The Role of Library Facilities and Infrastructure in Increasing Visitor Visits - Awalia Latifa Mayda Ikrimah; Angga Hadiapurwa; Gema Rullyana; Diemas Arya Komara (Literatify: Trends in Library Developments, 2023)
Introduction. As one of the supporters of learning activities whose existence we often encounter in every school, the library is intended to support teaching and learning activities. This study aims to determine the role of library facilities and infrastructure in increasing interest in visiting Taruna Bakti students.Research methods. The research method used is a qualitative research method with a case study type. Researchers conducted observations, interviews, and descriptive analysis.Analysis data. Researchers conducted data analysis through three stages: data reduction, data presentation, conclusions, and verification.Results and Discussion. The Taruna Bakti Foundation library has almost met the standards for the procurement of library facilities and markets based on indicators adapted by researchers from the Regulation of the Head of the National Library of the Republic of Indonesia Number 12 of 2017 concerning National Standards for High School/Madrasah Aliyah Libraries so that the Taruna Bakti Foundation Library can make users comfortable and increase visitor visits.